The Doping Mechanism of Halide Perovskite Unveiled by Alkaline Earth Metals - Phung, Nga; Félix, Roberto; Meggiolaro, Daniele; Al-Ashouri, Amran; Sousa E Silva, Gabrielle; Hartmann, Claudia; Hidalgo, Juanita; Köbler, Hans; Mosconi, Edoardo; Lai, Barry; Gunder, Rene; Li, Meng; et al. (Journal of the American Chemical Society, 2020)
Halide perovskites are a strong candidate for the next generation of photovoltaics. Chemical doping of halide perovskites is an established strategy to prepare the highest efficiency and most stable perovskite-based solar cells. In this study, we unveil the doping mechanism of halide perovskites using a series of alkaline earth metals. We find that low doping levels enable the incorporation of the dopant within the perovskite lattice, whereas high doping concentrations induce surface segregation. The threshold from low to high doping regime correlates to the size of the doping element. We show that the low doping regime results in a more n-type material, while the high doping regime induces a less n-type doping character. Our work provides a comprehensive picture of the unique doping mechanism of halide perovskites, which differs from classical semiconductors. We proved the effectiveness of the low doping regime for the first time, demonstrating highly efficient methylammonium lead iodide based solar cells in both n-i-p and p-i-n architectures.
CRIS-Team Scopus Importer:2020-02-14